Ca 2+ and Na + dependence of 3-hydroxyglutarate-induced excitotoxicity in primary neuronal cultures from chick embryo telencephalons - Kölker, Stefan; Koehr, Georg; Ahlemeyer, Barbara; Okun, Jürgen G.; Pawlak, Verena; Hörster, Friederike; Mayatepek, Ertan; Krieglstein, Josef; Hoffmann, Georg F. (Pediatric research, 2002)
Glutaryl-CoA dehydrogenase deficiency (also known as glutaric aciduria type I) is an autosomal, recessively inherited neurometabolic disorder with a distinct neuropathology characterized by acute encephalopathy during a vulnerable period of brain development. Neuronal damage in this disease was demonstrated to involve N-methyl-d-aspartate (NMDA) receptor-mediated neurotoxicity of the endogenously accumulating metabolite 3-hydroxyglutarate (3-OH-GA). However, it remained unclear whether NMDA receptors are directly or indirectly activated and whether 3-OH-GA disturbs the intracellular Ca2+ homeostasis. Here we report that 3-OH-GA activated recombinant NMDA receptors (e.g. NR1/NR2A) but not recombinant α-amino-3-hydroxy-5-methyl-4-isoxazole propionate receptors (e.g. GluR-A/GluR-B) in HEK293 cells. Fluorescence microscopy using fura-2 as Ca2+ indicator revealed that 3-OH-GA increased intracellular Ca2+ concentrations in the presence of extracellular Ca2+ in cultured chick neurons. Similar to glutamate-induced cell damage, 3-OH-GA neurotoxicity was modulated by extracellular Na+. The large cation N-methyl-d-glucamine, which does not permeate NMDA receptor channels, enhanced 3-OH-GA-induced Ca2+ increase and cell damage. In contrast, 3-OH-GA-induced neurotoxicity was reduced after replacement of Na+ by Li+, which permeates NMDA channels but does not affect the Na+/Ca2+ exchanger in the plasma membrane. Spectrophotometric analysis of respiratory chain complexes I-V in submitochondrial particles from bovine heart revealed only a weak inhibition of 3-OH-GA on complex V at the highest concentration tested (10 mM). In conclusion, the present study revealed that NMDA receptor activation and subsequent disturbance of Ca2+ homeostasis contribute to 3-OH-GA-induced cell damage.
Im Titel sind "2+" und "+" hochgestellt
Gesehen am 28.12.2020